2017
DOI: 10.1371/journal.pone.0183077
|View full text |Cite
|
Sign up to set email alerts
|

Chronic unpredictable stress exacerbates surgery-induced sickness behavior and neuroinflammatory responses via glucocorticoids secretion in adult rats

Abstract: Accumulated evidence indicates that stress sensitizes neuroinflammatory responses to a subsequent peripheral immune challenge. The present study investigated whether chronic unpredictable stress (CUS) aggravated surgery-induced sickness behavior and neuroinflammatory processes via glucocorticoids secretion in the adult brain.MethodsSprague-Dawley adult male rats (12–14 weeks old) were exposed to 14-day CUS and then subjected to partial hepatectomy 24 h after the last stress session. The rats were pretreated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Rats were treated 1 h before each stressful activity with vehicle or RU486 via subcutaneous injection at a volume of 1 mg/kg/day over a six-week uCMS exposure period. The dose of RU486 and timing prior to each experience of stress were based on two previous studies [45,46].…”
Section: Methodsmentioning
confidence: 99%
“…Rats were treated 1 h before each stressful activity with vehicle or RU486 via subcutaneous injection at a volume of 1 mg/kg/day over a six-week uCMS exposure period. The dose of RU486 and timing prior to each experience of stress were based on two previous studies [45,46].…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study revealed that surgery-induced proinflammatory cytokines in the brain of aged rats play an important role in the development of POCD [2, 7, 21]. These earlier findings suggest that neuroinflammatory response may be an important underlying mechanism for POCD.…”
Section: Introductionmentioning
confidence: 96%
“…Additionally, Rosczyk et al have demonstrated that locomotor activity is not depressed in either adult or aged mice following sham operation (minor abdominal surgery), which reveals that the decrease in locomotion is not due to minor surgical procedures [20]. It is likely that a more “major” surgery (partial hepatectomy) would induce a state of neuroinflammation that could result in sickness behavior [2, 7, 21-25]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, following a single session of inescapable tail shock stress, rats exhibit elevated hippocampal IL-1β production in response to intra-peritoneal LPS (Johnson et al, 2002; Johnson et al, 2003). Although LPS is commonly used as the immune challenge, stress also potentiates pro-inflammatory cytokine responses in the CNS following other peripheral and central immune challenges such as surgery or ischemic injury (Karelina et al, 2009; Norman et al, 2010; Wang et al, 2017; Weil et al, 2008). Potentiated neuroinflammatory responses follow a diverse array of stressors including chronic variable stress (de Pablos et al, 2014; Espinosa-Oliva et al, 2011; Yue et al, 2017), social defeat (Wohleb et al, 2012), stress from shipping/travel (Holder and Blaustein, 2017), social isolation (Gaudier-Diaz et al, 2017), chronic sleep restriction (Bellesi et al, 2017), and inescapable tail shock (Frank et al, 2007; Johnson et al, 2002) suggesting that neuroinflammatory priming may be a conserved feature of the stress response.…”
Section: Neuroinflammatory Priming Elicited By Stress and Agingmentioning
confidence: 99%